S-allyl Cysteine and Taurine revert peripheral metabolic and lipid profile in non-insulin-dependent diabetes mellitus animals: Combination vs Monotherapy - Nadeem Rais; Kehkashan Parveen; Rizwan Ahmad; Waseem Ahmad Siddiqui; Ayasha Nadeem; Akash Ved (Universidade de São Paulo, 2023)
Abstract The present study was designed to evaluate the beneficial synergistic effects of S-allyl Cysteine (SAC) and Taurine (TAU) on hyperglycemia, lipid profile and renal damage markers in type 2 diabetes mellitus (T2DM) in rats. Experimental T2DM was developed by administering an intraperitoneal single dose of nicotinamide (NA; 230 mg/kg) and streptozotocin (STZ; 65 mg/ kg) in adult rats. Control and diabetic rats were treated with SAC (150 mg/kg); TAU (200 mg/ kg) or SAC and TAU (75+100 mg/kg) combination for four weeks. Measurements of traditional markers of kidney toxicity in serum, such as blood urea nitrogen (BUN), serum creatinine (Scr), and alkaline phosphatase (ALP), together with serum cholesterol/triglyceride such as serum total cholesterol (TC), triglycerides (TG), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C) and very low-density lipoprotein cholesterol (VLDL-C) may yield a snapshot of renal damage and lipid profile in NA/STZ-treated rats. The variation in levels of fasting blood glucose, glycosylated hemoglobin, insulin and lipid profile was significantly augmented in SAC/TAU treatment group. The diabetic group showed elevated renal injury markers in serum, which were decreased significantly by SAC/TAU treatment. Thus the results of the experiment clearly indicate the potential of the SAC/TAU combination in improving diabetic complications.